Religion and Social Cooperation : Results from an Experiment in Ghana - Parra, Juan Carlos; Joseph, George; Wodon, Quentin (Taylor and Francis, 2016)
The international community recently adopted the Sustainable Development Goals (SDGs). Achieving these goals by 2030 will require major commitments and efforts. It will also require cooperation between multiple groups and stakeholders, both nationally and internationally. An interesting question is whether religious diversity and the evocation of religion tend to be conducive to “social cooperation” between individuals from various religious traditions. We refer here to social cooperation in a fairly broad sense, but we focus in this paper on specific measures of altruism and trustworthiness between individuals of various different religious affiliations.